Penerapan Mesin Daur Ulang Sampah Plastik Menggunakan Metode Fuzzy Tsukamoto Berbasis Teknologi Internet Of Things (Iot) - Sahtyawan, Rama; Wibowo, Teguh; Sahudi, Suwarno (Institut Teknologi Dirgantara Adisutjipto, 2025)
This research aims to design an Internet of Things (IoT)-based plastic waste recycling machine using the Fuzzy Tsukamoto method to overcome the problem of overheating in electric motors and improve waste management efficiency. The methods used include literature studies, designing a microcontroller-based system (ESP32), temperature sensors, inductive proximity sensors, and implementing the Fuzzy Tsukamoto algorithm for automatic temperature control. The results show that the machine is capable of shredding plastic with a capacity of 20 kg/hour and controlling the motor temperature in real-time through the MIT Inventor application. Tests prove that the motor temperature rises faster during shredding (30°C–55°C in 35 minutes) compared to no-load (90 minutes). The system also successfully detects metal and stops operation automatically to prevent damage. The conclusion of the study states that the integration of IoT and Fuzzy Tsukamoto is effective in optimizing machine performance, reducing the risk of overheating, and facilitating remote monitoring. Suggestions for further development include improving the cooling system and sensor calibration for long-term stability.